THE INFLUENCE OF INTANGIBLE FACTORS ON THE POTENTIAL DEVELOPMENT OF THE ECONOMIES OF THE MOSCOW REGION AND THE KRASNODAR TERRITORY - A. Nazarov (Вестник университета)
The article discusses issues related to the system of strategic planning and improvement of regional economies with the influence of intangible factors on the development of the territorial economy.